Synthesis and antibacterial activity of 3-arylaminomethyl-1-(2-oxo-2-arylethyl)-6,7,8,9-tetrahydro-5H-[1,2,4]triazolo[4,3-a] azepin-1-ium bromides and aryl-(4-R1-phenyl-5,6,7,8-tetrahydro-2,2a,8a-triazacyclopenta[cd]azulen-1-ylmethyl)-amines - Demchenko, Nataliya; Suvorova, Zinaida; Fedchenkova, Yuliia; Shpychak, Tamara; Shpychak, Oleh; Bobkova, Ludmila; Demchenko, Sergii (ScienceRise: Pharmaceutical Science, 2021)
The aim of this work is to develop methods of synthesis of 3-arylaminomethyl-1-(2-oxo-2-arylethyl)-6,7,8,9-tetrahydro-5H-[1,2,4]triazolo[4,3-a]azepin-1-ium bromides and aryl-(4-R1-phenyl-5,6,7,8-tetrahydro-2,2a,8a-triazacyclopenta[cd]azulen-1-ylmethyl)-amines and to study their antimicrobial activity against strains of gram-positive and gram-negative bacteria as well as yeast fungi. Materials and methods. 1Н NMR spectra were recorded on Bruker 400 spectrometer operating at frequency of 400 MHz. Antimicrobial activity of the compounds synthesized was evaluated by their minimum inhibitory concentration (MIC) values. Results and discussion. The interaction of 3-arylaminomethyl-6,7,8,9-tetrahydro-5H-[1,2,4]triazolo[4,3-a]azepines with substituted phenacyl bromides produced novel 3-arylaminomethyl-1-(2-oxo-2-arylethyl)-6,7,8,9-tetrahydro-5H-[1,2,4]triazolo[4,3-a]azepin-1-ium bromides. The latter when refluxed in 10 % solution of NaOH gave aryl-(4-R1-phenyl-5,6,7,8-tetrahydro-2,2a,8a-triazacyclopenta[cd]azulen-1-ylmethyl)-amines. The study of antimicrobial activity of the compounds obtained allowed to find derivatives which are active against С. albicans and S. aureus strains. Among the compounds tested 3-[(41-bromophenylamino)-methyl]-1-[2-(4-methoxyphenyl)-2-oxoethyl]-6,7,8,9-tetrahydro-5H-[1,2,4]triazolo[4,3-a]azepin-1-ium bromide 5cd appeared to be more active than the reference drug Cefixime and displayed close antimicrobial activity as the antibiotic Linezolid. Conclusions. It was found out that derivatives of 3-arylaminomethyl-1-(2-oxo-2-arylethyl)-6,7,8,9-tetrahydro-5H-[1,2,4]triazolo[4,3-a]azepin-1-ium bromides display broad spectrum of antimicrobial activity and are able to inhibit growth of both bacteria and fungi. S. aureus and C. albicans turned out to be the most sensitive strains to the compounds tested, MIC was in the range of 6.2-25.0 mg/mL. Gram-negative strains of microorganisms were less sensitive to the compounds evaluated and 5fа was the most active derivative displaying antimicrobial activity at the concentration of 50.0 mg/mL. Antimicrobial activity of triazoloazepinium bromide derivatives was similar to that one of Linezolid and Fluconazole reference drugs and more pronounced than the activity of Cefixime. Hence, the data gathered evidence the feasibility of further study of the antimicrobial properties of the most active compounds in in vivo experiments aiming at assessment of the prospects for the creation of new effective and safe antimicrobial drugs based on them